Acute Toxicity and DNA Instability Induced by Exposure to Low Doses of Triclosan and Phthalate DEHP, and Their Combinations, in vitro - Duarte, Nathalia de Assis Aguilar; Lima, Lindiane Eloisa de; Maraslis, Flora Troina; Kundi, Michael; Nunes, Emilene Arusievicz; Barcelos, Gustavo Rafael Mazzaron (Frontiers in Genetics, 2021)
Triclosan (TCS) is an antimicrobial agent widely used in personal care products (PCPs) and the di-(2-ethyl hydroxy-phthalate) (DEHP) is a chemical compound derived from phthalic acid, used in medical devices and plastic products with polyvinyl chloride (PVCs). As result of their extensive use, TCS and DEHP have been found in the environment and previous studies demonstrated the association between their exposure and toxic effects, mostly in aquatic organisms, but there is a shortage in the literature concerning the exposure of TCS and DEHP in human cells. The aim of the present study was to assess the impact of exposure to TCS and DEHP, as well as their combinations, on biomarkers related to acute toxicity and DNA instability, in HepG2 cells, by use of cytokinesis-block micronucleus cytome (CBMNCyt) assay. For that, the cultures were exposed to TCS, DEHP and combinations at doses of 0.10; 1.0 and 10 μM for the period of 4 hours and the parameters related to DNA damage (i.e., frequencies of micronuclei (MN) and nuclear buds (NBUDs), to cell division (i.e., nuclear division index (NDI) and nuclear division cytotoxic index (NDCI) and to cell death (apoptotic and necrotic cells) were scored. Clear mutagenic effects were seen in cells treated with TCS, DEHP at doses of 1.0 and 10 μM, but no combined effects were observed when the cells were exposed to the combinations of TCS + DEHP. On the other hand, the combination of the toxicants significantly increased the frequencies of apoptotic and necrotic cells, as well as induced alterations of biomarkers related to cell viability (NDI and NDCI), when compared to the groups treated only with TCS or DEHP. Taken together, the results showed that TCS and DEHP are also able to induce acute toxicity and DNA damage in human cells.